Characterization and micromechanical modelling of microstructural heterogeneity effects on ductile fracture of 6xxx aluminium alloys. (15th January 2016) - Hannard, F.; Pardoen, T.; Maire, E.; Le Bourlot, C.; Mokso, R.; Simar, A.
Abstract: Ductile failure of three 6xxx serie aluminium alloys has been characterized and modelled for about thirty hardening conditions each. These alloys involve relatively similar composition and volume fraction of second phase particles. The tensile mechanical properties show the expected decrease of fracture strain with increasing strength but also major differences among the different alloys with a factor ten in terms of reduction of area at fracture between best and worst case. The origin of these differences is unraveled by detailed characterization of the void nucleation, growth and coalescence process involving in situ 3D microtomography. A cellular automaton model, involving a high number of particles with distributions of position, sizes and void nucleation stress is developed to predict the fracture strain. Excellent predictions are obtained based on the same unique nucleation stress distribution versus particle size for the three alloys. The key element setting the fracture strain is the effect of particle size distribution and spatial distribution on the void nucleation and coalescence processes. The dependence of ductility on strength is properly captured as well. Graphical abstract: